2015
DOI: 10.1111/jpn.12353
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance of layer chickens reared on deep litter system with or without access to grass or legume pasture

Abstract: Despite several studies carried out to investigate the effects of access to pasture on poultry performance, there is a dearth of information on the comparative benefit of grass and legumes. This study investigated the effects of rearing systems [deep litter system (DL), deep litter with access to legumes (LP) or grass (GP) pastures] on the performance of ISA Brown layers. Two hundred and forty 12-week-old pullets were housed for this study. They were reared until 60 weeks of age. Eighty birds were assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
4

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 12 publications
3
13
4
Order By: Relevance
“…Albumen is an important determining factor for internal egg quality. A higher albumen height and Haugh unit indicates better egg quality (Şekeroǧlu & Altuntaş, 2009;Oke et al, 2014). The albumen height and Haugh unit determines the viscosity of the thick albumen (Hanusova et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Albumen is an important determining factor for internal egg quality. A higher albumen height and Haugh unit indicates better egg quality (Şekeroǧlu & Altuntaş, 2009;Oke et al, 2014). The albumen height and Haugh unit determines the viscosity of the thick albumen (Hanusova et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Kralik et al (2017) state that HU values range between 70.36 and 71.33, which are lower compared with the results obtained in the present study (80.81 and 83.99 for conventional and designer eggs, respectively). Oke et al (2014) found that eggs produced in different rearing systems presented 66.86-71.41 HU, with higher values obtained in younger than in older layer flocks. Hanusova et al (2015) point out that the internal quality of eggs depends on their freshness and, therefore, it is the best to consume eggs immediately after lay.…”
Section: Physical-chemical Characteristics Of Designer and Conventionmentioning
confidence: 91%
“…Also, weather elements, such as extreme temperatures, light intensity and photoperiod, are uncontrollable in pastured poultry (Fanatico et al, 2005;Wang et al, 2009). Our previous studies (Oke et al, 2016) indicated that the performance of laying hens on legume pasture (Stylosanthes hamata) was better than grass pasture (Cynodon dactylon). Additionally, Ponte et al (2008) indicated that pasture intake improved the performance of broiler chickens.…”
Section: Introductionmentioning
confidence: 98%
“…Poultry performance is influenced by the environment (Oke et al., 2016). Essentially, housing systems are necessary to protect birds from rain, physical hazards and extreme cold and heat (Panda, 1985).…”
Section: Introductionmentioning
confidence: 99%